Simulation-Based Countermeasures Towards Accident Prevention : Virtual Reality Utilization in Industrial Processes and Activities - Kwegyir-Afful, Ebo (Vaasan yliopisto, 2022)
Despite growing industrial interests in fully immersive virtual reality (VR) applications for safety countermeasures, there is scanty research on the subject in the context of accident prevention during manufacturing processes and plant maintenance activities. This dissertation aims to explore and experiment with VR for accident prevention by targeting three workplace safety countermeasures: fire evacuation drills, hazard identification and risk assessments (HIRA), and emergency preparedness and response (EPR) procedures. Drawing on the virtual reality accident causation model (VR-ACM) (i.e., 3D modelling and simulation, accident causation, and safety drills) and the fire evacuation training model, two industrial 3D simulation models were utilized for the immersive assessment and training. These were a lithium-ion battery (LIB) manufacturing factory and a gas power plant (GPP). In total, five studies (publications) were designed to demonstrate the potential of VR in accident prevention during the manufacturing processes and maintenance activities at the facility conceptual stages. Two studies were with the LIB factory simulation to identify inherent hazards and assess risks for redesigning the factory to ensure workplace safety compliance. The other three studies constituted fire hazard identifications, emergency evacuations and hazard control/mitigations during the maintenance activity in the GPP simulation. Both study models incorporated several participants individually immersed in the virtual realm to experience the accident phenomena intuitively. These participants provided feedback for assessing the research objectives. Results of the studies indicated that several inherent hazards in the LIB factory were identified and controlled/mitigated. Secondly, the GPP experiment results suggested that although the maintenance activity in the virtual realm increased the perception of presence, a statistically significant delay was recorded at the pre-movement stage due to the lack of situational safety awareness. Overall, the study demonstrates that participants immersed in a VR plant maintenance activity and manufacturing factory process simulation environments can experience real-time emergency scenarios and conditions necessary for implementing the essential safety countermeasures to prevent accidents.

Vaikka kiinnostus virtuaalitodellisuuden (VR) käyttöön turvallisuuden varotoimissa teollisuudessa on kasvanut, tutkimuksia ei ole juurikaan tehty onnettomuuksien ehkäisystä valmistus- ja kunnossapitotoiminnassa. Tämän väitöskirjan tavoitteena on tutkia ja kokeilla VR:ää tapaturmien ehkäisyssä kohdistuen kolmeen työpaikan turvallisuuden varotoimeen: paloharjoitukset, riskien arvioinnit sekä hätätilanteiden valmiusmenettelyt ja toimintasuunnitelmat (EPR). Kokemuksellisessa ja uppouttavassa koulutuksessa hyödynnettiin kahta teollisuuden 3D-simulointimallia, jotka nojautuvat virtuaalitodellisuuden onnettomuuksien aiheutumismalliin (VR-ACM) (eli 3D-mallinnus- ja simulointi, onnettomuussyy- ja turvallisuuskoulutus) sekä paloharjoitusmalliin. Nämä 3D-simulointimallit ovat litiuminoniakkuja (LIB) valmistava tehdas, joka rakennettiin Visual Components 3D-simulointiohjelmistolla (versio 4.0) ja kaasuvoimala (GPP) Unrealin reaaliaikaisella pelimoottorilla (versio 4.2). Yhteensä viisi tutkimusta (julkaisua) suunniteltiin havainnollistamaan VR:n potentiaalia tapaturmien ehkäisyssä valmistusprosessin layout-suunnittelun ja tehtaan konseptivaiheissa tehtävän kunnossapidon aikana. Kaksi tutkimusta tehtiin LIB-tehdassimulaatiolla vaarojen tunnistamiseksi sekä riskien arvioimiseksi. Tutkimukset tehtiin tehtaan uudelleensuunnittelua varten, työturvallisuuden noudattamisen varmistamiseksi. Muut kolme tutkimusta käsittelevät palovaaran tunnistamista, hätäevakuointia ja riskien vähentämistä huoltotoiminnan aikana GPP-simulaatiossa. Molemmissa tutkimusmalleissa oli useita virtuaalimaailmaan uppoutuneita osallistujia, jotka saivat kokea onnettomuudet yksilöllisesti ja intuitiivisesti. Osallistujat antoivat palautetta kokeen jälkeisessä kyselyssä. Kyselyn tuloksien avulla LIB-tehtaassa tunnistettiin ja lievennettiin useita vaaroja. GPP-kokeilun tulokset viittasivat siihen, että vaikka ylläpitotoiminta virtuaalimaailmassa lisäsi teleläsnäoloa, tilastollisesti merkittävä viive kirjattiin liikettä edeltävässä vaiheessa turvallisuustietoisuuden puuteen vuoksi. Kaiken kaikkiaan tutkimus osoittaa, että VR-laitoksen kunnossapitotoimintaan ja tuotantotehtaan prosessisimulaatioympäristöihin uppoutuvat osallistujat voivat kokea reaaliaikaisia hätäskenaarioita ja olosuhteita, jotka ovat välttämättömiä olennaisten turvallisuustoimien toteuttamiseksi.
Keywords: simulation; virtual reality; accident prevention; technology; safety and security; industrial safety; accidents; risk assessment; control (prevention); disasters; fi=Tuotantotalous|en=Industrial Management|